The effect of ESG on firm value through cost of debt: The moderating role of independent assurance - Hanafi, Muhammad Lutfi; Pramono, Hadi; Fakhruddin, Iwan; Pramurindra, Rezky (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
This study examines the association between ESG disclosure and firm value among energy sector companies listed on the Indonesia Stock Exchange over 2019 to 2023, using 226 firm year observations, with Cost of Debt as a mediator and Independent Assurance as a moderator. Panel regression was processed using EViews and Stata, with models estimated using the Fixed Effect Model with White diagonal standard errors for consistency, supplemented by bootstrapped confidence intervals for the mediation test. Results show ESG disclosure is positively associated with Cost of Debt, contrary to expectations, while Cost of Debt is negatively associated with firm value and ESG disclosure is positively associated with firm value. Cost of Debt significantly mediates this relationship, with direct and indirect pathways running in opposite directions, indicating competitive mediation. Independent Assurance does not significantly moderate the ESG and Cost of Debt relationship. Firm size and the pandemic period are included as controls.